Context-dependent female mate choice maintains variation in male sexual activity. Issue 7 (12th July 2017) - Sommer-Trembo, Carolin; Plath, Martin; Gismann, Jakob; Helfrich, Claudia; Bierbach, David
Abstract : The existence of individual variation in males' motivation to mate remains a conundrum as directional selection should favour high mating frequencies. Balancing selection resulting from (context-dependent) female mate choice could contribute to the maintenance of this behavioural polymorphism. In dichotomous choice tests, mosquitofish ( Gambusia holbrooki ) females preferred virtual males showing intermediate mating frequencies, reflecting females' tendencies to avoid harassment by highly sexually active males. When tested in the presence of a female shoal—which protects females from male harassment—focal females showed significantly stronger preferences for high sexual activity. A trade-off between (indirect) benefits and (direct) costs of mating with sexually active males probably explains context-dependent female mate choice, as costs depend on the social environment in which females choose their mates. No preference was observed when we tested virgin females, suggesting that the behavioural pattern described here is part of the learned behavioural repertoire of G. holbrooki females.